Polysaccharides from Laminaria japonica: an insight into the current research on structural features and biological properties. Issue 10 (27th April 2021) - Luan, Fei; Zou, Junbo; Rao, Zhili; Ji, Yafei; Lei, Ziqin; Peng, Lixia; Yang, Yan; He, Xirui; Zeng, Nan
Abstract : A comprehensive review on extraction, separation, and purification methods, structural characteristics, biological activities, clinical settings, toxicities, and structure–activity relationships of Laminaria japonica polysaccharides. Abstract : Laminaria japonica, one of the most widespread seafood consumed in China and many other nations, has been traditionally utilized as an effective therapeutically active substance for treating weight loss, phlegm elimination, and detumescence for more than 2000 years. Numerous studies have found that the polysaccharides play an indispensable role in the nutritional and medicinal value of L. japonica . Water extraction and alcohol precipitation method is the most used method. Approximately 56 LJPs were successfully isolated and purified from L. japonica, whereas only few of them were well characterized. Modern pharmacological studies have shown that L. japonica polysaccharides (LJPs) have high-order structural features and multiple biological activities, including anti-tumor, anti-thrombotic, anti-atherosclerosis, hypolipidemic, hypoglycemic, antioxidant, anti-inflammatory, renoprotective, and immunomodulatory. In addition, the structural characteristics of LJPs are closely related to their biological activity. In this review, the extraction and purification methods, structural characteristics, biological activities, clinical settings, toxicities, and structure–activity relationships of LJPs are comprehensively summarized. The structural characteristics and biological activities as well as the underlying molecular mechanisms of LJPs were also outlined. Furthermore, the clinical settings and structure–activity functions of LJPs were highlighted. Some research perspectives and challenges in the study of LJPs were also proposed.